2010
DOI: 10.1152/ajplung.00089.2009
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow-derived angiogenic cells restore lung alveolar and vascular structure after neonatal hyperoxia in infant mice

Abstract: Neonatal hyperoxia impairs vascular and alveolar growth in mice and decreases endothelial progenitor cells. To determine the role of bone marrow-derived cells in restoration of neonatal lung structure after injury, we studied a novel bone marrow myeloid progenitor cell population from Tie2-green fluorescent protein (GFP) transgenic mice (bone marrow-derived angiogenic cells; BMDAC). We hypothesized that treatment with BMDAC would restore normal lung structure in infant mice during recovery from neonatal hypero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
78
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(83 citation statements)
references
References 66 publications
(88 reference statements)
3
78
1
1
Order By: Relevance
“…However, in this study, we found that in the late phase of BPD, a single dose of EPCs administered through the peripheral venous route only increased lung microvessels, with no improvement in alveolar structure as determined by RAC measurements. Compared with the two previous studies (9,10), the reason why mono-EPCs treatment did not result in any improvement in alveolar structure could be due to the selected route of administration.…”
Section: Combined Epc Transplantation and Ino Improved Lung Structurecontrasting
confidence: 68%
See 1 more Smart Citation
“…However, in this study, we found that in the late phase of BPD, a single dose of EPCs administered through the peripheral venous route only increased lung microvessels, with no improvement in alveolar structure as determined by RAC measurements. Compared with the two previous studies (9,10), the reason why mono-EPCs treatment did not result in any improvement in alveolar structure could be due to the selected route of administration.…”
Section: Combined Epc Transplantation and Ino Improved Lung Structurecontrasting
confidence: 68%
“…The distal lung harbors EPCs (27) that contribute to lung repair, and their depletion in the developing lung is associated with arrested lung development (28,29). Studies showed that provided angiogenic cells could promote alveolar and vascular growth after neonatal hyperoxic exposure, and restore lung structure to normal in infant mice (9). However, in this study, we found that in the late phase of BPD, a single dose of EPCs administered through the peripheral venous route only increased lung microvessels, with no improvement in alveolar structure as determined by RAC measurements.…”
Section: Combined Epc Transplantation and Ino Improved Lung Structurementioning
confidence: 99%
“…[147][148][149][150] However, administration of conditioned medium from mesenchymal cells can provide similar levels of protection. 149 Furthermore, newborn rats treated with cord blood MSCs display attenuated pulmonary myeloperoxidase, IL-6, TNF␣, and transforming growth factor ␤ expression.…”
Section: Interruption Of Key Components Of the Inflammatory Cascadementioning
confidence: 99%
“…These progenitor cells seem to play a most important role here, and this may apply to premature infants [7], children with severe lung disease [8] and, perhaps, also adults [9]. Other findings, such as observations that CHSPCs are increased in menstruating females who exhibit a cyclic increase of diffusing capacity [10], and that infusion of angiogenic cells helps to restore alveolar development in a mouse model of bronchopulmonary dysplasia [11], also strongly suggest that angiogenic cells play a role in developing or restoring the pulmonary vasculature and may enhance alveolar formation indirectly.In addition, these observations are in line with older studies. A large interindividual variability in the number of alveoli was recognised decades ago [12][13][14] and one can speculate that this is partly due to biological variation in the numbers and/or ratio of pro-and non-angiogenic CHSPCs.…”
mentioning
confidence: 87%